Glacier Calving Rates Due to Subglacial Discharge, Fjord Circulation, and Free Convection. Issue 9 (15th September 2018) - Schild, K. M.; Renshaw, C. E.; Benn, D. I.; Luckman, A.; Hawley, R. L.; How, P.; Trusel, L.; Cottier, F. R.; Pramanik, A.; Hulton, N. R. J.
Abstract: Tidewater glacier calving provides the most direct mechanism of ice transfer from land to the ocean. However, the physical melt processes influencing calving remain challenging to constrain. In this study we focus on calving rates at Kongsbreen, a tidewater glacier in Svalbard, due to three mechanisms of submarine melt: (1) free convection, (2) horizontal fjord circulation, and (3) meltwater discharge. To calculate an overall calving rate, we measure glacier velocity and terminus change using Sentinel imagery. We calculate free convection, fjord circulation, and meltwater discharge calving using mooring data for mid‐fjord ocean temperature (30–80 m depth), reanalysis results for meltwater runoff, and georectified time‐lapse imagery to track icebergs and infer surface circulation. Results show that the total glacier calving rate is highly correlated with ocean temperature during the 2016 melt season. When runoff was present, we found that subglacial discharge accounted for calving rates an order of magnitude greater than the maximum calving rates assigned to the other two melting mechanisms combined. Further, subglacial discharge at Kongsbreen was more efficient in inducing calving later in the season than earlier in the season, implying that the increase in ocean temperatures, the timing of meltwater discharge within a melt season, and/or the development of discrete meltwater exit channels are critical components to calving rates. As the recent atmospheric warming trend and subsequent increase in meltwater discharge is expected to continue, it is essential to understand the processes contributing to an increase in glacier calving and incorporate these processes into predictive models. Key Points: We partition calving rate due to submarine melt into calving due to free convection, horizontal fjord circulation, and meltwater discharge The calving rate due to meltwater discharge is up to an order of magnitude larger than fjord circulation and free convection calving rates A given flux of meltwater has a greater impact on calving rate at the end of the melt season than in the early melt season